Cyber Politic as A New Perspective for People in Surabaya in Understanding Politics in the Digital Age - Lisaria Putri, Rumanintya; Chasan Amrulloh, Muhammad; Gunawan, Alvien; Sunandes, Aris; Agustin Widhi Yanti, Dyah (KnE Social Sciences, 2023)
Cyber politic is a set of data, graphical representations, that can only be accessed through computers. Septanto describes cyber politic as an internet technology that develops to pay attention to the phenomenon of beliefs that arise from various social media. This study aims to identify a new perspective on the relationship between politics and digital media for the people of Surabaya in understanding cyber politics in the digital age. This study uses a descriptive qualitative approach and data collection conducted by the author through desk research, namely data collected based on existing sources. The analysis of the theory used is the effectiveness theory, interactive technology, network communication, and the internet. The results of this study show that cyber politic can be a new network communication that facilitates the electoral process in the digital age at this time. Cyber politic was created to provide convenience for every individual because many people today benefit from technology in finding sources of information, especially in politics. Keywords: Cyber Politic, Technology, Interactive